Relatório de Estágio Profissionalizante realizado no Lusitânia de Lourosa Futebol Clube, Juvenis A (Sub-17) masculina, na época desportiva 2023/2024 - Fernando César Matos Maia (2024)
Current football is characterized by the constant search for sporting performance and its enhancement. These goals require an increased professionalization and a higher range of skills in the different aspects related to the sport. At a time when every detail is relevant, the role of the coach is of major importance, who must present a wide repertoire of skills, in addition to technical-tactical issues, including management, leadership and communication skills. This document refers to the professional internship which took place in the U19 men's team of Lusitânia de Lourosa Futebol Clube during the 2023/2024 season, in the context of the 2nd cycle in Sports Training, specialization in High Performance Training, at the Sports Faculty of University of Porto. This aims to describe and critically reflect about the experiences lived during this process, the skills acquired and all the elements that influenced my activity as a coach. Regarding the structure of the report, it is initially composed of a more theoretical part, introduction and conceptual macro-context, followed by practical contextualization, a chapter describing in detail the development of the practice, professional development and final considerations. Lastly, there will be bibliographic references and attachments. In this sequence, my functions as an intern coach and physical trainer are discribed, critically reflecting on my performance and aspects linked to the entire experience. In this way, it will be possible to observe the approach to different topics within the sport, from the game model and its training process, the coach's leadership and communication and also an aspect mainly directed towards the physical dimension.